Effectiveness of Digital Payments in the Performance of Nepalese Micro, Small and Medium Enterprises (MSME) - Bhattarai, Birat; Shrestha, Riya; Maharjan, Sejal; Malla, Shristina; Shakya, Saksham (New Perspective: Journal of Business and Economics, 2023)
This study aims to examine the effectiveness of digital payments on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Nepal. The research is based on a survey of 118 MSMEs within the Kathmandu Valley. Correlation, regression analysis, and ANOVA were used to analyze the data and draw conclusions. The findings indicate that the frequency of use of digital payments, perceived usefulness, perceived security, and ease in making payments to suppliers/creditors have a significant impact on the firm’s performance. However, digital literacy and ease in accepting payments from customers/debtors do not have a significant influence on firm performance. This finding contradicts previous research conducted in different contexts and suggests that being digitally literate does not necessarily translate into the use of digital payments for business transactions. The study highlights the importance of understanding the usage of digital payments across different types of enterprises, such as MSMEs, and calls for further research to explore this topic using secondary data. Additionally, the study suggests that future research should expand beyond the Kathmandu Valley to gain a more comprehensive understanding of the topic.